Developing a River Health Index: A Study in Ylang-Ylang River, Cavite, Philippines - Martinez, K A S (KnE Social Sciences, 2018)
This study explored the possibility of bridging the gap of inadequate assessment of rivers by considering the measurement of river health by developing a river health (RH) index. RH assessment is a crucial component of the strategy to protect, conserve and enhance the Philippine river systems. Through developing an integrative RH index, it can provide a systematic and standardized method of assessment which encompasses not only the physico-chemical aspects of rivers in terms of water quality but also their biological components. Participatory approach among experts was considered to come up with the weights and arrive with the scoring scheme for each identified indicators and sub-indicators of RH. Primary data from Ylang-Ylang River were gathered following standard sampling protocol and species identification. The study reveals that the current system of assessment of rivers in the Philippines focuses only on water quality and generally does not consider the assessment of biological indicators which are significant gauge of a river’s ecological integrity – river health. The level of significance in indicating RH between physico-chemical and biological parameters is equally important based on experts’ opinion. The developed RH index is recommended to be utilized by several government agencies and private institutions to practice holistic river monitoring towards sustainability. The developed RH index can be applied to other rivers in the Philippines or even other countries. Improvement of this study may include the specification of the frequency of collecting the primary data and consideration of social aspects. Keywords: river health, water quality, biological indicators, index